(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Human papillomaviruses (HPVs) are epitheliotropic viruses with an affinity for keratinocytes and are principally found in the anogenital tract, urethra, skin, larynx, tracheobronchial and oral mucosa. On the basis of high, but variable frequency of HPV in oral squamous cell carcinoma (OSCC), malignant potential of HPV infection has been hypothesized but not definitely confirmed. The aim of this review was to highlight the genomic structure and possible mechanism of infection and carcinogenesis by HPV in the oral mucosa and to review the frequency of HPV prevalence in OSCC and oral potentially malignant disorders. A computer database search was performed through the use of PubMed from 1994 to 2014. Search keywords used were: HPV and oral cancer, HPV and oral leukoplakia, HPV and oral lichen planus, HPV and OSCC, HPV and verrucous carcinoma, HPV and proliferative verrucous leukoplakia, HPV and oral papilloma.